Implementation Of Group Discussion Method In Fiqh Learning To Improve Understanding Of Islamic Law At SMP Ma’arif NU Riyadus Sholihin Yosowilangun - Kurniawan, Ifan; Mukhsin, Mukhsin (Yayasan Rahmat Islamiyah, 2025)
This study examines the application of group discussions in learning Fiqh at Ma'arif NU Riyadus Sholihin Yosowilangun Junior High School with the aim of identifying obstacles and assessing their effectiveness in improving understanding of Islamic law. This study uses a descriptive qualitative approach and data triangulation through interviews, observation, and documentation, the data is analyzed based on the Miles and Huberman interactive model. The results show that the group discussion, which is carried out systematically including the preparation, implementation and closing stages, contributes significantly to improving learning motivation, concept mastery, learning outcomes, and student confidence. The main obstacles found include imbalance in participation, limited learning time, and variations in students' initial understanding.